2011
DOI: 10.1007/s11524-011-9591-4
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Risk Behaviors among Inner-City African-American Adolescents

Abstract: Adolescents tend to experience more problems with sleep loss as a natural consequence of puberty, whereas teens from impoverished urban areas are likely to witness neighborhood violence and/or engage in risk behaviors that may affect sleep. Data from the Mobile Youth Survey, a longitudinal study of impoverished inner-city African-American adolescents (1998-2005; N=20,716; age range=9.75-19.25 years), were used to compare paired years of annual surveys elicited by questions about how sleep was affected when bad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 44 publications
4
21
1
Order By: Relevance
“…These findings provide compelling support for the role of social-cognitive processes in understanding how violence exposure can impact sleep functioning. In another longitudinal study, Umlauf et al (2015) extended previous work with the Mobile Youth Survey (Umlauf et al 2011) by showing violence exposure and hopelessness to have independent and multiplicative effects on adolescent sleep trajectories, with trauma-exposed females at particular risk for subsequent sleep problems related to traumatic stress. These studies provide excellent examples of integrating the community context into models of adolescent sleep.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 74%
See 2 more Smart Citations
“…These findings provide compelling support for the role of social-cognitive processes in understanding how violence exposure can impact sleep functioning. In another longitudinal study, Umlauf et al (2015) extended previous work with the Mobile Youth Survey (Umlauf et al 2011) by showing violence exposure and hopelessness to have independent and multiplicative effects on adolescent sleep trajectories, with trauma-exposed females at particular risk for subsequent sleep problems related to traumatic stress. These studies provide excellent examples of integrating the community context into models of adolescent sleep.…”
Section: Overview Of Special Issue Contributionsmentioning
confidence: 74%
“…Longitudinal data also speak to the link between sleep problems and adolescents carrying or using weapons. In a large sample of inner-city African American adolescents, Umlauf et al (2011) found traumagenic-related sleep problems (i.e., difficulty sleeping or experiencing nightmares due to bad things happening to a family member or friend) to be longitudinally associated with carrying, brandishing, and using a knife or gun, as well as endorsing aggressive and violent attitudes in response to disrespect or personal affront, even after controlling for exposure to violence and traumatic stress. In addition, seeing someone cut, stabbed, or shot, alcohol use, worry, and internalized anger were each longitudinally associated with sleep disturbance (Umlauf et al 2011).…”
Section: Neighborhood and Community Factorsmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, for many students English was not their first language, and the current study was not able to evaluate if this had any influence on interpretation of questions and student responses. The present study focused on the effects of aggression on sleep problems; however, there is evidence suggesting that the association between aggression and sleep difficulties is bidirectional in nature (Dahl and Harvey 2007;Gregory and Sadeh 2012;Umlauf et al 2011). Additionally, symptoms of anxiety and reactive aggression are likely contributing to one another (Marsee et al 2008).…”
Section: Discussionmentioning
confidence: 88%
“…For instance, the combined public health costs of the obesity epidemic in children and adolescents and its associated cardiovascular morbidities are estimated at $45 billion a year, and sleep loss is longitudinally associated with increased risk of obesity in children and adolescents (Magee et al, 2012). Further, insufficient sleep among teens is associated with an increased risk of engaging in property and violent crime (Umlauf et al, 2011). The direct and indirect costs of crime, including direct economic losses, increased insurance rates, loss of productivity, and various aspects of the criminal justice system, from police, to courts, to juvenile facilities and prisons, are estimated in the billions of dollars (NCJRS, 2000).…”
Section: Discussionmentioning
confidence: 99%